STUDIES ON THE EFFECT OF VARIOUS ADDITIVES ON THERMOSTABLE PROTEASE EXTRACTED FROM ZINGIBER OFFICINALE RHIZOME - NEETU JABALIA,; P.C. MISHRA,; NIDHEE CHAUDHARY, (International Journal of Pharma and Bio Sciences, 2016)
Zingiber officinale is one of the richest sources of proteolytic enzymes; which further have great potential in industries. In the present study, protease extracted from Z. officinale has been characterized biochemically with respect to various additives viz; metal ions, detergents and organic solvents. The pH stability of protease ranged from 4.0 to 6.0 and exhibited thermostability upto 500C. Out of the cations tested in the form of their respective salts; K+>Na+>Zn2+>Cu2+ were found have stimulatory effect ranging upto 15% in descending order. On the contrary, Mn2+>Co2+>Fe3+ inhibited the protease activity. Mn2+ showed maximum inhibitory effect upto 35% showing its great potency. On treatment with various organic solvents (0.1%), all except toluene inhibited the protease activity upto 30%. Out of detergents tested at 0.1%, Tween-80 acted as strongest inhibitor showing upto 80% decrease in activity followed by Tween-20 (40% inhibition) while Triton X-100 and Sodium Lauryl Sulphate (SLS) acted as activators.